The Value of Spiral Chest Computed Tomography Scan in the Diagnosis of Asymptomatic Coronavirus Carriers among Paranasal Sinus and Pharynx Surgery Candidates - Hasibi,Mehrdad (2022)
Abstract Introduction The nasopharynx and oropharynx are the main colonization sites of coronavirus. Therefore, patients with paranasal sinuses and pharyngeal problems (ear, nose, and throat [ENT] patients) predispose coronavirus infection. Ear, nose, and throat patients with concomitant asymptomatic coronavirus infection may develop severe pneumonia following surgical procedures. As a result, presurgical screening for coronavirus infection is a substantial concern. Objective We evaluated the usefulness of a spiral chest computed tomography (CT) scan in the diagnosis of asymptomatic coronavirus infection in the presurgical assessment of ENT patients Methods In this study, candidates of paranasal sinus or pharyngeal surgery were evaluated for coronavirus infection. Patients with neither history of coronavirus disease 2019 (COVID-19) nor compatible symptoms and signs were screened for asymptomatic coronavirus infection. These patients composed two groups: the first group underwent a reverse transcription polymerase chain reaction (RT-PCR) test of nasopharyngeal sample and spiral chest CTscan, but for the second one, only the latter was performed. Results In the first group, which consisted of 106 patients, 11 (10.4%) cases had positive RT-PCR test results, and 17 (16%) patients showed positive findings in favor of coronavirus infection in the spiral chest CT scan. In the second group, which consisted of 173 patients, 34 (19.7%) cases had positive chest CT scan results. Conclusion The chest CT scan has a valuable role in the early diagnosis of asymptomatic coronavirus carriers in patients highly predisposed to infection, especially in low resource areas, where the RT-PCR test is unavailable.